Protective effects of conventional and colon-targeted lycopene and linalool on ulcerative colitis induced by acetic acid in rats - Tekeli, Ibrahim Ozan; Atessahin, Ahmet; Sakin, Fatih; Aslan, Abdullah; Ceribasi, Songul; Yipel, Mustafa (Springer Basel Ag, 2019)
ObjectiveTo compare the potential protective effects of conventional and colon-targeted lycopene (TLC) and linalool (TLN) on acetic acid (AA)-induced ulcerative colitis (UC) in rats.MethodsConventional and colon-targeted LC (10mg/kg) and LN (200mg/kg) were administered in vivo orally for 7days and sulfasalazine (100mg/kg) was also used as reference drug. Then, 4% AA was administered intrarectally to induce UC. Subsequently, the colon tissues were taken as samples for biochemical and histopathological analysis.ResultsMalondialdehyde (MDA), interleukin 1 (IL-1), IL-6, cyclooxygenase-2 (COX-2) and nuclear factor kappa B (NF-B) levels were decreased (p<0.05) in the targeted groups compared to the AA group, whereas nuclear factor-erythroid 2-related factor 2 (Nrf-2) level was increased (p<0.05). Tumor necrosis factor (TNF-) level was also decreased (p<0.05) and catalase activity (CAT) was increased (p<0.05) in the TLC group compared to the AA group. IL-1 and IL-6 levels were lower in the TLC group compared to the conventional LC and sulfasalazine groups (p<0.05). COX-2 and NF-B levels were lower, while the Nrf-2 level was higher in the targeted groups compared to the conventional groups (p<0.05). Furthermore, COX-2 level was lower and Nrf-2 level was higher in the targeted groups compared to the sulfasalazine group (p<0.05).ConclusionAs expected, sulfasalazine was effective on all parameters analyzed, but the colon-targeted pretreatments were more effective from sulfasalazine on some parameters. Therefore, colon-targeted plant-derived therapies might be alternative approaches to provide protection against UC, which deserves to be investigated further.
Keywords: Ulcerative colitis; Colon targeting; Lycopene; Linalool; Rat